Sosialisasi Penggunaan Alat Pelindung Diri (APD) sebagai Upaya Pencegahan K3 terhadap Pekerja Bangunan di Kecamatan Medan Tembung - Cece Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was conducted by lecturers from STIM Sukma in October 2025 at Medan Tembung District. The aim was to enhance the awareness and understanding of construction workers regarding the importance of using Personal Protective Equipment (PPE) as a preventive measure against occupational accidents. Ten construction workers participated in the socialization activity, which included interactive lectures, group discussions, and simple demonstrations on the proper use of PPE. The results indicated a positive improvement in workers’ knowledge and awareness toward PPE use, although some limitations were observed regarding tool availability and habitual work behaviors. This activity highlights the significance of an educational and humanistic approach in cultivating a culture of safety within the informal construction sector. Through follow-up programs and regular mentoring, it is hoped that changes in worker behavior will develop more consistently. Furthermore, collaboration with local stakeholders is crucial to ensure the availability of PPE and the desire for a culture of workplace safety within the community.